Marketing Applications of the Analytic Hierarchy Process - Wind, Yoram; Saaty, Thomas L. (Management Science, 1980)
Several marketing applications of the Analytic Hierarchy Process (AHP) are reviewed. The paper starts with a brief description of this process, which was developed by Thomas Saaty in 1971, including an eight-point outline of how to apply it. The thrust of the paper is a discussion of a number of illustrative applications of the AHP covering the following areas: the portfolio decisions of a firm whose management is concerned with the determination of the desired target portfolio and allocation of resources among its components, determination of the directions for new product development, and generation and evaluation of marketing mix strategies. Various suggestions for additional research on the AHP and its marketing applications are highlighted.